Taxation, Business Environment and FDI Location in OECD Countries - Hajkova, Dana (OECD Publishing, 2006)
This paper assesses the importance of taxation on foreign direct investment contributing to the literature in two ways. First, it relates bilateral FDI among OECD countries over the 1990s to a new set of estimates of corporate tax wedges that include many relevant aspects of FDI taxation. Second, it controls for a large set of additional policy and non-policy factors that may affect the attractiveness of a country for foreign investors. Furthermore, the empirical approach is novel in that it focuses on a semi-parametric estimation methodology that accounts for a number of unobserved effects possibly impinging on the choice of investment location by multinational enterprises. Consistent with previous findings, the estimation results suggest that corporate taxation has a non-negligible impact on FDI location choices. However, the results suggest that focusing only on taxation in home and host countries and omitting other policies (such as border policies and labour and product market settings) may lead to a serious overestimation of tax elasticities and their relevance for policy
Keywords: Economics